The association between school bullying and internet addiction among adolescents: a moderated mediation model - Li, Lei; Cai, Jia; Wang, Cong; Mu, Yun-Fei; Deng, Zhong-Yue; Deng, Ai-Ping; Song, Hong-Jun; Huang, Xue-Hua; Yin, Li; Huang, Yi; Chen, Jin; Zhao, Jun-Shu; et al. (Frontiers in Public Health, 2025)
BackgroundSchool bullying poses a serious threat to the mental well-being of adolescents. Although previous research has demonstrated a link between school bullying and internet addiction, the psychological mechanism remains poorly understood. This study aimed to explore the mediating roles of depressive and anxiety symptoms, as well as the moderating role of the stigma of mental illness.MethodsA cross-sectional survey among 82,873 middle and high school, college, and university students in Sichuan Province, China, was conducted for this study. Moderated mediation models were examined using PROCESS macros in SPSS 26.0.ResultsThe school bullying was positively correlated with internet addiction, with depression and anxiety symptoms partially mediating internet addiction, respectively. The stigma of mental illness significantly moderated this relationship, revealing a stronger association between school bullying, depression and anxiety symptoms, and internet addiction for adolescents with higher levels of stigma.ConclusionsThese findings emphasize the importance of addressing depressive and anxiety symptoms as well as stigma of mental illness in interventions to prevent school bullying and internet addiction. Programs tailored to these factors are crucial for alleviating the negative impacts of school bullying on the mental health and online behaviors of adolescents.